2020
DOI: 10.1155/2020/8309745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Massage on the TLR4 Signalling Pathway in Rats with Neuropathic Pain

Abstract: This study set out to investigate the effect of massage on the Toll-like receptor 4 (TLR4) signalling pathway in the dorsal root ganglia of rats that had undergone spinal nerve ligation (SNL), with the hypothesis that massage could be used as an analgesic. Forty female SD rats were randomly divided into 5 groups: the control group, sham-operated group, model group, sham massage group, and massage group. There were 8 rats in each group. SNL rat models were established in the model group, sham massage group, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…The high levels of inflammatory cytokines in elderly individuals [28] are considered to be caused by underlying inflammatory diseases. Recent findings suggest that a reduction in the release of inflammatory cytokines via the inhibition of the TLR4 signaling pathway may be a mechanism by which massage can relieve neuropathic pain [48]. Atanackovic et al [40] demonstrated a marked but short-term increase in IL-6 and TNFα levels in patients with malignant diseases during the first 5-24 h after whole-body hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of inflammatory cytokines in elderly individuals [28] are considered to be caused by underlying inflammatory diseases. Recent findings suggest that a reduction in the release of inflammatory cytokines via the inhibition of the TLR4 signaling pathway may be a mechanism by which massage can relieve neuropathic pain [48]. Atanackovic et al [40] demonstrated a marked but short-term increase in IL-6 and TNFα levels in patients with malignant diseases during the first 5-24 h after whole-body hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…If a rat lifted or licked its paw three or more times under the filament stimulation, the result was regarded as positive; otherwise, it was deemed negative. The force that triggered a positive reaction was considered the PWMT (He et al., 2010; Wang et al., 2020). The test was finished when a positive reaction was observed.…”
Section: Methodsmentioning
confidence: 99%
“…If a rat lifted or licked its paw 3 or more times under the lament stimulation, the result was regarded as positive; otherwise, it was negative. The force that triggered a positive reaction was called PWMT (He et al 2010;Wang et al 2020). The test was nished when a positive reaction was observed.…”
Section: Pwmtmentioning
confidence: 99%